Development of a persistent-mode NMR magnet with superconducting joints between high-temperature superconductors. (17th September 2021) - Yanagisawa, Y; Piao, R; Suetomi, Y; Yamazaki, T; Yamagishi, K; Ueno, T; Takao, T; Ohki, K; Yamaguchi, T; Nagaishi, T; Kitaguchi, H; Miyoshi, Y; et al.
Abstract: This paper describes the first persistent-mode medium magnetic field (400 MHz; 9.39 T) nuclear magnetic resonance (NMR) magnet which uses superconducting joints between high-temperature superconductors (HTSs). As the ultimate goal, we aim to develop a high-resolution 1.3 GHz (30.5 T) NMR magnet operated in the persistent-mode. The magnet requires superconducting joints between HTSs and those between an HTS and a low-temperature superconductor (LTS). Towards this goal, we have been developing persistent-mode HTS inner coils to be operated in a 400 MHz (9.39 T) NMR magnet and here we present the first prototype inner coil wound with a single piece (RE = rare earth)Ba2 Cu3 O7− x (REBCO) conductor. The coil and a REBCO persistent current switch are connected with intermediate grown superconducting joints with high critical currents in external magnetic fields. To evaluate the performance of the joints in an ultimately stable and homogeneous magnetic field, the coil is operated in the persistent-mode, generating 0.1 T, in a 9.3 T background magnetic field of a persistent-mode LTS outer coil. The magnetic field drift over two years of the 400 MHz LTS/REBCO NMR magnet is as small as ∼1 ppm, giving high-resolution NMR spectra. The magnetic field drift rate over the second year was 0.03 × 10 −3 ppm h −1, which is more than three orders of magnitude smaller than that required for an NMR magnet, demonstrating that the superconducting joints function satisfactorily in a high-resolution NMR system. The corresponding joint resistance is inferred to be <10 −14 Ω.